The Mediating Role of Emotional Regulation in the Relationship Between Emotional Abuse and Subjective Well-Being - V, Sindhu; N, Maheshbabu (Journal of Neonatal Surgery, 2025)
Adolescence is a critical developmental period marked by emotional, cognitive, and social transformations, during which subjective well-being (SWB) plays a pivotal role in healthy adjustment and performance. Emotional abuse—defined as non-physical behaviors that humiliate, threaten, or isolate—can significantly influence adolescents' emotional functioning and psychological health. Emotional regulation (ER), which encompasses implicit and explicit strategies to monitor and modify emotional responses, is considered a key mediator in the relationship between adverse experiences and well-being. This study examined the mediating role of emotional regulation in the relationship between emotional abuse and subjective well-being among adolescents across genders. A sample of 268 adolescents aged 12–15 years (grades 6–10) was selected through convenience sampling. A 3x1 factorial research design was adopted. Standardized tools were used: the Emotional Abuse Questionnaire (Momtaz et al., 2021), the Subjective Well-being Inventory (Nagpal & Sell, 1985), and the Adolescent Emotion Regulation Questionnaire (Kostiuk, 2011). Path analysis was conducted to test the mediational model. The results indicate that Emotional Abuse does not have a significant direct effect on Subjective Well-being (p = 0.341), supporting the idea that emotional abuse influences well-being indirectly through emotional regulation. A significant positive relationship was found between Emotional Abuse and Emotional Regulation (β = 6.072), showing that higher levels of emotional abuse lead to greater difficulties in regulating emotions. Emotional Regulation was found to mediate the impact of Emotional Abuse on Subjective Well-being, particularly affecting emotional outcomes like PA and NA. Emotional Abuse negatively influenced PA (-0.123) and positively influenced NA (0.237), suggesting that emotional abuse exacerbates negative emotional states while hindering the ability to experience positive emotions. Furthermore, Emotional Abuse impaired Positive Emotion Regulation Strategies (-3.675), and was linked to negative psychological outcomes such as Negative Body Image (-2.460) and reduced Social Connection (-2.075). The findings underscore the mediating role of emotional dysregulation in the impact of Emotional Abuse on well-being.